(untitled) (Bangladesh Journal of Neurosurgery, 2023)
Sphenoid-orbital meningiomas (SOMs) are difficult to completely resect because they involve the sphenoid wing, orbit, and cavernous sinus. As the tumor invades the optic canal, SOMs frequently present with visual deficits. The authors of this case report dealt with the case of a 65-year-old male patient who had right-sided proptosis. We diagnosed the patient, and his MRI revealed of him having SOM. The surgical approach was determined by the tumor’s placement in the orbit and cranial cavity and its connections to the optic canal and optic nerve axis. Tumor was removed successfully by surgery. The patient retained a proptosis of less than 4 mm during the follow-up period. The visual acuity, visual field, and ocular fundus were examined during the follow-up. SOMs are notoriously difficult to treat surgically. The primary goal of surgery in symptomatic individuals with SOMs is to slow down the tumor’s progression. Longer periods of post-operative follow-up is recommended to observe long-term results. Bang. J Neurosurgery 2022; 12(1): 65-68